Prospects of using security mechanism in the process of rehabili-tation the building sphere in Ukraine - Krekoten, Iryna; SvÑ–stun, Lyudmyla; Khudolii, Yulia (International Journal of Engineering and Technology, 2018)
In this article, securitization was investigated as one of the most important sources of financing for the construction of residential real estate in Ukraine. The main purpose of the article is to explore ways to refinance mortgage loans used in the world practice for the rehabilitation the building sphere in residential real estate and to identify ways of expanding and cheapening them. The authors have found that a depository financing model uses on the Ukrainian mortgage market has significantly reduced the possibilities for its development and makes the mortgage expensive. Also, the models of the European and American mortgage markets were compared, identified the advantages and disadvantages of each model. And the possibility of using these models in Ukraine was considered. The current state of the mortgage market in Ukraine was examined. In addition, the trend of mortgage market development in a pre-crisis and post-crisis period was demonstrated in this article. Finally, the following conclusion was drawn: in order to increase the availability of mortgage loans and to rehabilitation the construction sphere, it is necessary to introduce mechanisms for refinancing mortgage loans.Â Â